MicroRNA global profiling in cystic fibrosis cell lines reveals dysregulated pathways related with inflammation, cancer, growth, glucose and lipid metabolism, and fertility: an exploratory study. - Catellani, Cecilia; Cirillo, Francesca; Graziano, Sara; Montanini, Luisa; Marmiroli, Nelson; Gullì, Mariolina; Street, Maria Elisabeth (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Cystic fibrosis (CF), is due to CF transmembrane conductance regulator (CFTR) loss of function, and is associated with comorbidities. The increasing longevity of CF patients has been associated with increased cancer risk besides the other known comorbidities. The significant heterogeneity among patients, suggests potential epigenetic regulation. Little attention has been given to how CFTR influences microRNA (miRNA) expression and how this may impact on biological processes and pathways. Methods: We assessed the changes in miRNAs and subsequently identified the affected molecular pathways using CFBE41o-, and IB3 human immortalized cell lines since they reflect the most common genetic mutations in CF patients, and 16HBE14o- cells were used as controls. Results: In the CF cell lines, 41 miRNAs showed significant changes (FC (log2) ≥ +2 or FC (log2) ≤ -2 and p-value≤0.05). Gene target analysis evidenced 511 validated miRNA target genes. Gene Ontology analysis evidenced cancer, inflammation, body growth, glucose, and lipid metabolism as the biological processes most impacted by these miRNAs. Protein-protein interaction and pathway analysis highlighted 50 significantly enriched pathways among which RAS, TGF beta, JAK/STAT and insulin signaling. Conclusions: CFTR loss of function is associated with changes in the miRNA network, which regulates genes involved in the major comorbidities that affect CF patients suggesting that further research is warranted.